2015
DOI: 10.1039/c4ra12105h
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of structural and thermal properties of carbon-coated TaC nanopowder synthesized by single step reduction of Ta-ethoxide

Abstract: Carbon-coated nano-TaC has been synthesized at 800 °C using tantalum-ethoxide by single step chemical reaction route and no external carbon source

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…The N 2 adsorption-desorption isotherm becomes a type II isotherm and the hysteresis loop disappears in the middle relative pressure. [30] It can be seen from the pore size distribution map inserted in the figure that the micropore Table S1, it can be found that the specific surface area, the micropore volume and the total pore volume of the Fe/AC desulfurizer are reduced, and the average pore diameter is increased. It may be due to the formation of elemental S, iron sulfide and sulfate in the pores of the desulfurizer after desulfurization of Fe/AC, causing clogging of the desulfurizer channel.…”
Section: N 2 Adsorption-desorption Analysis Of Fe/ac Desulfurizersmentioning
confidence: 96%
“…The N 2 adsorption-desorption isotherm becomes a type II isotherm and the hysteresis loop disappears in the middle relative pressure. [30] It can be seen from the pore size distribution map inserted in the figure that the micropore Table S1, it can be found that the specific surface area, the micropore volume and the total pore volume of the Fe/AC desulfurizer are reduced, and the average pore diameter is increased. It may be due to the formation of elemental S, iron sulfide and sulfate in the pores of the desulfurizer after desulfurization of Fe/AC, causing clogging of the desulfurizer channel.…”
Section: N 2 Adsorption-desorption Analysis Of Fe/ac Desulfurizersmentioning
confidence: 96%
“…Tantalum carbide (TaC) has attractive physical and chemical properties such as a high melting point, high modulus, and hardness values, good ductile behavior at high temperature, high chemical stability, and excellent resistance to oxidation. These properties make TaC a promising material for many applications such as metallic materials reinforcement, electronic devices, rocket nozzle and scramjet component, catalyst support material for ammonia decomposition and acidic‐polymer‐electrolyte membrane for water electrolyzers . A TaC coating on metallic materials can endow the substrate with remarkable properties while preserving its nature.…”
Section: Introductionmentioning
confidence: 99%
“…These properties make TaC a promising material for many applications such as metallic materials reinforcement, electronic devices, rocket nozzle and scramjet component, catalyst support material for ammonia decomposition and acidicpolymer-electrolyte membrane for water electrolyzers. [1][2][3][4][5] A TaC coating on metallic materials can endow the substrate with remarkable properties while preserving its nature. Especially, a layer of tantalum carbide can provide other materials an opportunity to be used as high temperature structural materials.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous reports, we have successfully synthesized various transition‐metal carbides (TMCs) viz. Mo 2 C, NbC, WC, VC, TaC, and Cr 3 C 7 in a specially designed autoclave at low temperatures. Magnesium (Mg) as a reducing agent plays a vital role during the synthesis of TMCs.…”
Section: Introductionmentioning
confidence: 99%